2016
DOI: 10.1111/bjhp.12189
|View full text |Cite
|
Sign up to set email alerts
|

Habitual instigation and habitual execution: Definition, measurement, and effects on behaviour frequency

Abstract: Objectives'Habit' is a process whereby situational cues generate behaviour automatically, via activation of learned cue-behaviour associations. This article presents a conceptual and empirical rationale for distinguishing between two manifestations of habit in health behaviour, triggering selection and initiation of an action ('habitual instigation'), or automating progression through subactions required to complete action ('habitual execution'). We propose that habitual instigation accounts for habit-action r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
125
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 180 publications
(138 citation statements)
references
References 70 publications
2
125
0
2
Order By: Relevance
“…It seems plausible to relate this finding to previous work in behavioural science that has highlighted that forming habits , that is ingrained automatic routines initiated by environmental cues, may be important to maintaining long-term behaviour [37, 38]. Habits form through context-dependent repetition [39], and while initially effortful becomes easier if the action is repeated with sufficient consistency in the same position within one’s routine [40, 41].…”
Section: Discussionmentioning
confidence: 60%
“…It seems plausible to relate this finding to previous work in behavioural science that has highlighted that forming habits , that is ingrained automatic routines initiated by environmental cues, may be important to maintaining long-term behaviour [37, 38]. Habits form through context-dependent repetition [39], and while initially effortful becomes easier if the action is repeated with sufficient consistency in the same position within one’s routine [40, 41].…”
Section: Discussionmentioning
confidence: 60%
“…Kaushal, Rhodes, Meldrum, et al . () found that preparatory habit was a stronger determinant of physical activity than was performance habit, and studies have observed habitual instigation, but not execution, to predict behaviour frequency for dental hygiene, dietary consumption, and physical activity (Gardner et al ., ; Phillips & Gardner, ). Research is needed to replicate such findings across behaviours and contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions designed to encourage frequent performance need not promote rigid performance; while this may foster habitual execution, it is unlikely to enhance the likelihood of performance (Gardner et al ., ; Phillips & Gardner, ). Indeed, for strongly affect‐driven behaviours, such as physical activity (Rhodes, Fiala, & Conner, ), an action performed in the same way on each occasion may become unenjoyable and so be discontinued (Sylvester et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations